Two-dimensional shear wave elastography for significant liver fibrosis in patients with chronic hepatitis B: A systematic review and meta-analysis. Issue 124 (March 2020) - Wei, Hong; Jiang, Han-Yu; Li, Mou; Zhang, Tong; Song, Bin
Highlights: 2D SWE is beneficial for predicting significant fibrosis in CHB populations. The mean cutoff value of 2D SWE for diagnosing ≥ F2 was 7.91 kPa in overall patients with CHB. 2D SWE showed a mean threshold of 7.15 kPa for diagnosing ≥ F2 in antiviral treatment-naïve patients with CHB. The cutoffs that account for antiviral therapy as a confounder need to be established. Abstract: Purpose: To determine the diagnostic performance and cutoff value of two-dimensional shear wave elastography (2D SWE) for detecting significant liver fibrosis in patients with chronic hepatitis B (CHB). Methods: A systematic literature search of the PubMed, EMBASE, Cochrane Library databases and Web of Science was conducted. Bivariate modelling and summary receiver-operating-characteristic (ROC) modelling were constructed to summarize the diagnostic performance of 2D SWE. Meta-regression analyses were performed to explore the source of heterogeneity. Results: Eleven eligible studies with 2623 patients were included. 2D SWE showed a summary sensitivity of 88 % (95 % CI: 83–91), specificity of 83 % (95 % CI: 78–88) and area under the ROC curve of 0.92 (95 % CI: 0.89–0.94) for detecting significant fibrosis in CHB patients. The mean threshold of 2D SWE was 7.91 kPa (range: 6.73–10.00 kPa). Notably, the cutoffs of studies excluding patients with history of prior antiviral therapy were generally lower than that of studies without excluding those who had received antiviral treatment, with an average of 7.15 kPa and 8.87 kPa, respectively (p < 0.01). Meta-regression analysis revealed that enrollment of consecutive patients was the only significant factor influencing heterogeneity (p < 0.01). Specifically, studies recruiting consecutive patients with CHB had significantly lower sensitivity than those with absence of consecutive enrolment (0.83 vs 0.92, p < 0.01). Conclusions: 2D SWE is an excellent modality for predicting significant liver fibrosis in CHB populations. Further work is required to establish the cutoffs that account for antiviral treatment as a potential confounding factor.